A new M & A methodology: five lessons in anticipating post-merger resource interactions and challenges. Issue 4 (20th July 2015) - Chatterjee, Sayan; Brueller, Nir N.
Abstract : Purpose: – The purpose of this paper is to develop a taxonomy of M & A that can be used to understand which type of M & A is likely to succeed. The taxonomy also allows managers to identify the integration imperatives that is so critical to success in M & A. Design/methodology/approach: – Grounded research and thick description of business situations. Findings: – This paper identifies the importance of analyzing the nature of the resource interactions that deliver value. If deal makers keep our advice in mind they should truly be able to improve the batting average above the historical norms. Research limitations/implications: – Even though we have studied a large number of M & A, this is not a typical lot sample quantitative study. It is possible to test the taxonomy on a large sample study if the M & A can be coded in to distinct groups. Practical implications: – When considering a merger or an acquisition, managers should be able to identify the type of M & A that corresponds to one of the categories in our taxonomy. This would allow managers to consider the general imperatives suggested in our paper for success. These general imperatives can then be modified for the unique situation faced by the manager. Social implications: – No direct implication except that societal resources will be used efficiently. Originality/value: – There are other typology/taxonomy in the literature. However, none to our knowledge uses the resource interaction lens.